Exosomes as Drug Delivery Vehicles for Cancer Treatment - Narayanan, Eshwaran (Current Nanoscience, 2020)
Exosomes are nanoscale extracellular vesicles that encapsulate a diverse range of biomolecules such as nucleic acids, proteins, and lipids. They are involved in several biological processes and mediate intracellular communication. Recent reports that they exhibit unique traits in pathological conditions have generated significant interest in employing them as diagnostic and therapeutic tools. Particularly, their potential to serve as drug delivery vehicles for the treatment of cancer and other diseases has been explored in numerous studies. This manuscript reviews recent developments in the field and discusses important considerations for further refinement of this approach and realization of more effective exosome-based drug delivery systems.
Keywords: nanotechnology